How Indonesian Students Use the Polya’s General Problem Solving Steps - Hari Pratikno; Endah Retnowati (Southeast Asian Mathematics Education Journal, 2018)
General problem-solving steps consist of understanding the problem, developing a plan, implementing the plan and checking the result. The purpose of this study is to explore how well Indonesia junior secondary school students apply these four steps in solving mathematical problems, especially on plane geometry topics. Using a qualitative approach, with a sample of nine students, of which three students were from the low mathematics achievement category, three from the medium and three from the high category, were given a test and instructed to write the answers to each question step by step. The results were described and categorized into four groups. The first group consisted of students who used all of the four steps. The second and the third were for students who used the first three steps or the first two steps respectively. The fourth group was for those who could only show the first step. The study indicated that for this sample the level of mathematic ability corresponded to how the students applied their problem-solving steps. It was found that students with high ability were included in the first group, while those with moderate ability were in the second group. Low ability students were categorized into group four. Nevertheless, there was one student with high ability who did not to do the checking step and there was one student with low ability who was able to develop a plan.